The Hippo pathway in endometrial cancer: a potential therapeutic target? - Shen, Xinyun; Li, Qianqian; Sun, Yiqing; Chen, Lingli; Xue, Fengxia; Tian, Wenyan; Wang, Yingmei (Frontiers in Oncology, 2023)
Endometrial cancer, one of the most prevalent malignant cancers tumors of the female reproductive tract, has been increasing in incidence and mortality rates around the world. The Hippo pathway, one of the eight traditional human cancer signaling pathways, is an intricate signaling network that regulates cell proliferation, differentiation, and migration as well as restricting organ size in response to a range of intracellular and extracellular signals. Inhibiting the Hippo pathway results in aberrant activation of its downstream core component YAP/TAZ, which can enhance cancer cells' metabolism and maintain their stemness. Additionally, the Hippo pathway can modulate the tumor microenvironment and induce drug resistance, where tumorigenesis and tumor progression occur. However, the Hippo pathway has been little researched in endometrial cancer. Here, we aim to review how the Hippo pathway contributes to the onset, development and the potential treatment of endometrial cancer with the aim of providing new therapeutic targets.